2020
DOI: 10.1016/j.heliyon.2020.e03898
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the protective potential of hydroalcoholic extract of Thymus daenensis on acetaminophen-induced nephrotoxicity in rats

Abstract: Background: Acetaminophen (APAP) is an antinociceptive and antipyretic drug that can be useful in therapeutic doses, although it can cause serious damage to the kidney if used overdose. The current study aimed to evaluate the protective effect of Thymus daenensis (TD) extract on APAP-induced kidney damage in rats. Methods: Thirty female Wistar rats were randomly divided into 5 groups: control, APAP (3 g/kg), TD (500 mg/kg), APAP þ TD (500 mg/kg), and APAP þ N-acetylcysteine (140 mg/kg). The APAP groups receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…The findings of the current study indicated that following the PCM administration (3 g/kg), serum urea and creatinine amounts increased significantly in comparison to the control group, which could indicate kidney tissue damage. These results were consistent with the findings of our previous study ( 13 ). Similar results were obtained in the previous studies by ingestion of 2 g/kg PCM ( 23 ).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The findings of the current study indicated that following the PCM administration (3 g/kg), serum urea and creatinine amounts increased significantly in comparison to the control group, which could indicate kidney tissue damage. These results were consistent with the findings of our previous study ( 13 ). Similar results were obtained in the previous studies by ingestion of 2 g/kg PCM ( 23 ).…”
Section: Discussionsupporting
confidence: 94%
“…T-SH contains protein thiol groups and GSH ( 29 ). Consistent with our previous study ( 13 ), in this work, it was observed that in rats treated with PCM, T-SH levels were significantly reduced, which could be due to GSH depletion by NAPQI. Similar to our previous study ( 8 11 )T-SH level enlarged in the SPE group in contrast to the PCM group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For example, the antagonist of β1-adrenergic receptors, nebivolol, decreases vascular MMP-2 activity and attenuates hypertension-induced vascular remodeling and collagen deposition by mechanisms apparently independent of β1 adrenoceptor-blocking properties, probably related to diminished NADPH oxidase activity decreasing ROS formation [ 103 , 106 ]. Additional examples of drugs exerting such beneficial pleiotropic effects include some dihydropyridines—such as nifedipine, nimodipine and amlodipine—which have antioxidant effects and downregulate MMP [ 130 , 131 , 132 ], or losartan, an antagonist of Ang-II type 1 receptors [ 133 ]. Other drugs with antioxidant effects, such as quercetin, also exert anti-MMP and anti-remodeling effects in hypertension [ 29 ].…”
Section: Mmp Inhibition As a Therapeutic Strategy To Prevent Vascular Remodeling In Hypertensionmentioning
confidence: 99%